Molecular regulation of cardiomyocyte functions by exogenous hydrogen sulphide in Atlantic salmon (Salmo salar) - Lazado, Carlo C.; Nhan, Thin Hoang; Voldvik, Vibeke; Burgerhout, Erik; Sundaram, Arvind; Tengs, Torstein; Østbye, Tone-kari K; Andersen, Øivind (Genomics, 2025)
Hydrogen sulphide (H2S) is known to regulate various physiological processes, but its role in fish cardiac function, especially at the molecular level, is poorly understood. This study examined the molecular functions of exogenous H2S, using sodium hydrosulphide (NaHS) as a donor, on Atlantic salmon cardiomyocytes. NaHS concentrations of 10 to 160 μM showed limited cytotoxicity and no impact on cell proliferation, though higher doses increased ATP activity. Menadione and NaHS administered separately or sequentially differentially regulated the expression of antioxidant response and sulphide detoxification genes. Transcriptomic analysis over 24, 48, 72, and 120 hours revealed differential gene expression related metabolic recovery. Enriched Gene Ontology terms at 24 hours included processes like cell signalling and lipid metabolism, shifting to lipid metabolism and ribosomal processes by 48 hours. By 120 hours, xenobiotic metabolism and RNA synthesis were prominent. The study highlights NaHS-induced metabolic adjustments, particularly in lipid metabolism, in Atlantic salmon cardiomyocytes. Molecular regulation of cardiomyocyte functions by exogenous hydrogen sulphide in Atlantic salmon (Salmo salar) publishedVersion